Special Examination Access History Management System of North Bangkok University - วิทยไพศาล สณัฐภูมิ; ดีเจริญชิตพงศ์ จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The Disciplinary Record and Special Examination Authorization System: A Case Study of North Bangkok University was developed to facilitate and streamline the operations of the Central Examination Committee. The system was built following the Systems Development Life Cycle (SDLC) Waterfall Model, which encompasses seven essential stages: Planning, Requirement & Analysis, System Design, System Development, System Testing, System Deployment, and Maintenance. The core functionalities of the system include recording student disciplinary history regarding regulatory violations prior to exams, summarizing the total number of students requesting special permission to enter examination rooms, and managing various data entries within the database. From a technical perspective, the system was developed using Visual Studio Code and utilizes MongoDB for database management. The target population for this study consisted of faculty members at North Bangkok University. A sample of 30 participants was selected through random sampling across seven faculties, including the Faculty of Business Administration, Information Technology and Digital Innovation, Liberal Arts, Political Science, Communication Arts, Education, and Nursing. Data collection and system quality evaluation were conducted through questionnaires distributed via Google Forms.